Mihrab design and ornamentation of selected mosques in Malaysia / Rosniza Othman - Rosniza, Othman (2011)
Mosque design should not be seen from just the external form, but the effective use of its interior should also be taken into consideration. This study is quite thorough in formulating a set of guiding principles through literature and site observations of selected mosques in Malaysia built from 1728 until 2005. Mihrab, which is contained in the Qibla wall, exists in almost all mosques built around the globe, carrying vital functions of orientating the Muslim prostration activities in mosques towards the Ka’aba in Mecca whilst providing the very own space for Imam in congregations. The methodology in this study is through plan analysis, observation and historical research. This thesis synthesizes Mihrab through the analysis of its design and ornamentation from the selected 23 historical and contemporary mosques in Malaysia. Firstly, this study looks at Mihrab as a focal point that needs to be emphasized with a high degree of visibility by examining the mosque layout especially at the prayer hall area, where prostration activities should be aided by mosques liturgical elements such as Mihrab and Qibla wall. Secondly, the evolution of Mihrab form is seen from the typological study that gives five styles of Mihrab applied in Malaysian mosques. Thirdly, observation on the ornamentation of Mihrab and Qibla wall has revealed that Malaysian mosques have their own tell tale motifs of vegetation that portray Malaysian identity in its own special way. The findings show that Malaysian Mihrabs and Qibla walls were not only styled with influences from abroad as there are styles uniquely originated and associated with the Malays. Study on Mihrab proves that cultural and social values of the local Muslims are still significant even though Malaysia perceived influences from Indians, Arabs and Chinese traders, including the British.